A novel lift-off diameter model for boiling bubbles in natural gas liquids transmission pipelines - Wenlong Jia; Youzhi Lin; Fan Yang; Changjun Li (Energy Reports, 2020)
The pipeline is a convenient and safe way to transport natural gas liquids (NGLs). However, the NGL is easy to boil due to the variations of pressures and temperatures along the pipeline. The bubble lift-off diameter is an essential parameter to calculate the mass and heat transfer rates between vapor and liquid phases for the NGL two-phase saturated boiling flow. This paper proposed a novel bubble lift-off diameter model based on the force-balance principle of bubbles, which considers the effects of the pressure, shear lift force, unstable drag force, surface tension, gravity force, buoyancy force, gas-phase density, bubble volume, bubble flow velocity, and bubble growth time on the bubble's lift-off diameters at various pipe inclination angles. A total of 136 experimental data points are applied to validate the new model. Results demonstrate that the average relative deviation (ARD) between the experimental bubble's lift-off diameters and calculated values based on the new model is in the range from 5.75% to 29.95%. In contrast, for horizontal and vertical pipes, the minimum ARDs of seven existing models (Fritz, Kocamustaf, Zeng, Lee, Situ, Hamzekhani, Chen models) are in the range from 19.42% to 42.58%, respectively. Moreover, the in-depth force analysis results reveal that the shear lift force, buoyancy force, drag force and surface tension force are dominant factors affecting the bubble lift-off diameters in inclined pipes. The new model provides an effective method to calculate the bubble lift-off diameter in the pipe at various inclination angles, overcoming the deficiencies of most existing models that only can be applied to either horizontal or vertical pipes.
Keywords: 330; Boiling flow; Bubble; Lift-off diameter; Natural gas liquids; Pipe